Microdosimetry with a 3D silicon on insulator (SOI) detector in a low energy proton beamline. (November 2020) - Samnøy, Andreas Tefre; Ytre-Hauge, Kristian S.; Malinen, Eirik; Tran, Linh; Rosenfeld, Anatoly; Povoli, Marco; Kok, Angela; Summanwar, Anand; Röhrich, Dieter
Abstract: Introduction: An accurate description of the radiation quality of proton beams is a precondition to increase our understanding of radiobiological mechanisms and to develop accurate biological response models for radiotherapy. However, there are few detectors capable of measuring microdosimetric quantities with high spatial resolution along the entire Bragg curve due to the rapid increase in stopping power at the Bragg peak (BP) and distal dose fall-off (DDF). The aim of this work was to measure the microdosimetric spectra along the Bragg curve in a low energy proton beamline used for radiobiological experiments with a novel 3D silicon-on-insulator (SOI) "mushroom" microdosimeter. Method: A silicon microdosimeter with an array of 3D structured diodes, creating well-defined sensitive volumes (SV) with excellent spatial resolution was used for microdosimetry. The microdosimeter was used to measure microdosimetric spectra and the relative dose throughout the Bragg curve of a 15 MeV proton beam by sequential insertion of 16 μm thick polyamide absorption films in front of the microdosimeter. The results were tissue corrected with a novel correction function and compared to Monte Carlo (MC) simulations performed in GATE. Results: The measured dose-mean lineal energy ( y D ‾ ) increased from 8 keV/μm at the entrance to 24 keV/μm at the BP, rising to a maximum of 35 keV/μm at the DDF. The measured y D ‾ showed an overall good agreement with the MC simulated values, with deviation of less than 2% at the BP and DDF, while the largest deviation (12%) was found at the entrance. Clear changes in microdosimetric spectra were seen for each 16 μm step at the BP and DDF. Conclusion: The SOI microdosimeter with its well-defined 3D sensitive volumes is an excellent tool for characterizing low energy beamlines that demands very high spatial resolution. The good overall agreement between experimental and simulated results indicated that the detector is capable of accurate microdosimetric measurements. Highlights: Silicon microdosimetry in proton beamline used for radiobiology experiments. Developed novel silicon to tissue correction function for proton therapy energies. Correction function significantly decreases uncertainty for low energy protons. Precise measurement at every 16 μm depth in polyamide absorbers at Bragg peak. Measured dose-mean lineal energy from 8 to 35 keV/μm.